Why Are Fewer Married Women Joining the Work Force in India? A Decomposition Analysis over Two Decades - Farzana Afridi; Taryn Dinkelman; Kanika Mahajan (Institute for the Study of Labor (IZA), 2016)
Unlike the global trend, India has witnessed a secular decline in women's employment rates over the past few decades. We use parametric and semi-parametric decomposition techniques to show that changes in individual and household attributes fully account for the fall in women's labor force participation rate in 1987-1999 and account for half of the decline in this rate in 1999-2009. Our findings underscore increasing education levels amongst rural married women and the men in their households as the most prominent attributes contributing to this decline. We provide suggestive evidence that a rise in more educated women's returns to home production, relative to their returns in the labor market, may have adversely affected female labor force participation rates in India.
Keywords: J21; J22; 330; female labor force participation; decomposition analysis; education; India